Overtones of Opera in American Literature from Whitman to Wharton - Skaggs, Carmen Trammell, 1976- (Book collections on Project MUSE., 2009)
Overtones of Opera explores the discourse of opera-both the art form and the social institution-in selected works of Whitman, Poe, Alcott, Chopin, Cather, James, and Wharton. For some, opera provided a powerful artistic medium for expressing a private aesthetic experience; in opera, they discovered the embodied voice of the artist. Others found not only the spectacle of opera but also its spaces, the opera houses and boxes, perfectly suited for displaying the class-based and commodity driven aspirations of America's new aristocracy. This noteworthy study will inform and enlighten literary scho.